PEMBERDAYAAN IBU PKK MELALUI PEMBUATAN JAMU HERBAL UNTUK MENINGKATKAN SISTEM IMUN TUBUH DI DESA ALUE SENTANG KABUPATEN ACEH TAMIANG - Fitriani Fitriani; Andri Yusman Persada; Juliati Juliati; Yulina Ismida (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Covid 19 is a disease caused by SARS-CoV-2 or known as a virus that can cause pneumonia, multi-organ failure, and death. Therefore, alternative efforts are needed to increase the body's immune system so that it can prevent viral infections in the body. One effort that can be done is to empower the people of Alue Sentang Village to make and consume herbal herbs which have the potential to increase endurance. Besides, it also increases the role and function of universities, Covid 19 volunteers, and village officials in accelerating and expanding the adoption of innovations in making herbal medicine to support the government in breaking the chain of the spread of Covid 19. The methods used in this activity are the direct approach method, lectures, and practice. The approach method was carried out by listing the problems faced by the people of Alue Sentang Village regarding the Covid 19 attack. The lecture method was carried out by providing information to the community, Covid 19 volunteers, and village officials about the advantages and benefits of herbal medicine in improving the immune system so that it could prevent and overcome Covid infection. 19. The practical method is carried out by providing training in making herbal herbwhich plays a role in increasing the immune system. The results achieved were the increased understanding and skills of PKK Alue Sentang Village women about making Herbal herbs to improve the immune system to control and prevent Covid-19.